Peningkatkan Kemampuan Menulis melalui Media Gambar Berseri dalam Pembelajaran Bahasa Inggris pada Siswa Kelas VIII SMPN Kelapa 2 Kabupaten Tangerang - Netty Rismayanti (LP4MK STKIP PGRI Lubuklinggau, 2021)
This classroom action research aims to improve writing skills through picture series media in learning English in class VIII students of SMPN Kelapa 2 Tangerang Regency. This research was carried out on class VIII students, totaling 35 students consisting of 15 male students and 20 female students. The research method used in this research is classroom action research using the spiral model of Kemmis and Mc Taggart. The stages of classroom action research according to Kemmis and Mc Taggart are planning, action, observation, and reflection. The increase in the writing test scores from the initial conditions to the first cycle to the third cycle, namely the average value in the initial conditions was 59.67 with a percentage of completeness 43.33% (18 people), in the first cycle increased to 65.33 with a percentage of completeness 60% ( 23 people), in the second cycle it increased to 72 with a completeness percentage of 73.33% (27 people), and in the third cycle it increased to 75.66 with a completeness percentage of 86.66% (31 people). The results obtained from classroom action research on 35 students, namely by increasing the average value from the initial conditions of 59.67, increasing to 65.33 in the first cycle, in the second cycle increasing to 72 and in the third cycle increasing to 75.66. It can be concluded that picture series media in learning English can improve the writing ability of class VIII students of SMPN Kelapa 2 Tangerang Regency. English teachers are expected to use and apply picture series media in the implementation of English learning on writing material in class. English teachers can use picture series media as learning media that can improve students' writing skills, so that students can easily develop their ideas or thoughts in writing.